Genome-wide characterization of R2R3-MYB gene family in Santalum album and their expression analysis under cold stress - Tang, Minqiang; Liu, Le; Hu, Xu; Zheng, Haoyue; Wang, Zukai; Liu, Yi; Zhu, Qing; Cui, Licao; Xie, Shangqian (Frontiers in Plant Science, 2023)
Sandalwood (Santalum album) is an important plant used worldwide for medicines and cosmetics. The R2R3-MYB gene family playes important roles in plant growth, development, and stresses resistance, and the members of R2R3-MYB genes were identified among different types of plants. However, genome-wide discovery of R2R3-MYB genes and their responses to cold stresses have not been reported in S. album. In this study, we identified the 114 R2R3-MYB genes at the whole genome level of S. album, investigated their characteristics and expression patterns under cold stress at different times. Results showed that 31 of 114 R2R3-MYB genes had significant expression differences under cold treatments. Transcriptome analysis and WGCNA demonstrated that three key candidate genes (SaMYB098, SaMYB015, and SaMYB068) were significantly related to cold treatments under different times in different modules. This study systematically analyzed the structural characteristics, systematic evolution, and expression patterns of R2R3-MYB genes under cold stress in S. album, which providing important information for further dissecting the function of R2R3-MYB genes and the mechanism of cold stress response in S. album.